A systematical study about the genus Lycopus L. (Labiatae) in Iraq (Baghdad Science Journal, 2025)
The study included gross morphology and pollen of plants – which collected during field trips , and dry ones for most specimen preserved with the Iraqi herbaria – related to the genus Lycopus L. , and to identify the unidentified species and rectify the error there in , so according to that the species L. europaeus L. only were specified for the genus . Through this work the varity L. europaeus var. glabrescens Schmidely were found at the first time , and suggested to record anew for Iraq . Pollen were of medium size, and had an ellipsoid shape in the equatorial view , and hexagonal in the polar view. The ecological and soil quality where these genus plants grows were specified , and were geographically distributed on natural Iraqi territories for each one .Plate was made from many pictures in addition to the map for geographical distribution.